Analisis Perbandingan Kinerja Seismik dari Struktur Gedung dengan Pelat Konvensional, Waffle Slab, dan Flat Slab - Yohanes Alexander Rupidara; Remigildus Cornelis; Tri M.W. Sir (Universitas Nusa Cendana, 2022)
Indonesia is a country with high earthquake risk because it is located in the path of the most active earthquake in the world. It makes Indonesia situated in a region with a high earthquake intensity. The study aimed to determine the seismic performance levels of building structures with conventional slabs, waffle slabs, and flat slabs with the time history analysis method. There are three models of structures studied, namely building structures with conventional plates, building structures with waffle slabs, and building structures with flat slabs, with a 5-story structure system, where the longest and shortest span has the same size of 20 m and the height of each level 4 m. This study showed the largest displacement was 235.82 mm in building structures with waffle slabs and the smallest displacement was 146.49 mm in building structures with flat slabs. The largest drift is 0.012 on a building structure with a waffle slab, and the smallest drift is 0.007 on a building structure with a flat slab. The level of seismic performance produced from all three types of structures varies from immediate occupancy (IO) to damage control (DC).